From awareness to action: evolving endocrinologist practices in obesity treatment in Italy - Chianelli, Marco; Busetto, Luca; Attanasio, Roberto; Guglielmi, Rinaldo; Cozzi, Renato; Grimaldi, Franco; Frasoldati, Andrea; Persichetti, Agnese; Papini, Enrico; Nicolucci, Antonio (Frontiers in Endocrinology, 2025)
IntroductionEarly treatment of obesity is essential and requires proactive engagement from healthcare providers. A 2022 survey among the members of the Italian Association of Clinical Endocrinologists (AME) revealed that they often did not address or manage the condition. This study aims to examine if attitudes and practices of Italian endocrinologists in managing obesity have changed in recent years, following several educational initiatives promoted by AME and the upcoming availability of specific treatments.MethodsThis research utilized a web-based survey distributed to members of AME. The survey explored endocrinologists’ approaches to obesity management, covering treatment methods, referral practices, and perceived challenges in providing effective care. At the time of the survey semaglutide and tirzepatide were not commercially available in Italy for the treatment of obesity/overweight.ResultsThe survey received responses from 16.6% of AME members (424 out of 2560). Among respondents, 32.5% 37 identified obesity and nutrition as key areas of focus. Among participants, 43.4% reported that over 35% of the patients they see each month have obesity, compared to 37.8% in the previous survey. The proportion of endocrinologists who reported managing obesity themselves, either independently or as part of a dedicated team, slightly increased from 42.6% 40 to 45.5%. In terms of pharmacological treatment, Liraglutide was prescribed to 25% of suitable patients (IQR 5-50), as compared to 10% (IQR 0-30) in the previous survey. Participants reported with less worries about side effects of treatment and patient resistance. Poor effectiveness almost disappeared among the reported obstacles to prescribing anti-obesity drugs. High treatment costs were cited as a primary barrier to prescribing anti-obesity medications, significantly affecting long-term adherence.DiscussionAddressing the unmet educational needs of endocrinologists is essential to enhance their awareness of obesity and increase their confidence in managing this widespread condition, which has a profound impact on individuals and society.